2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6638947
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition with deep recurrent neural networks

Abstract: Recurrent neural networks (RNNs) are a powerful model for sequential data. End-to-end training methods such as Connectionist Temporal Classification make it possible to train RNNs for sequence labelling problems where the input-output alignment is unknown. The combination of these methods with the Long Short-term Memory RNN architecture has proved particularly fruitful, delivering state-of-the-art results in cursive handwriting recognition. However RNN performance in speech recognition has so far been disappoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
4,082
2
27

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 7,175 publications
(4,124 citation statements)
references
References 20 publications
13
4,082
2
27
Order By: Relevance
“…However, growing evidence indicates that sequence specificities can be more accurately captured by more complex techniques [2][3][4][5] . Recently, 'deep learning' has achieved record-breaking performance in a variety of information technology applications 6,7 . We adapted deep learning methods to the task of predicting sequence specificities and found that they compete favorably with the state of the art.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…However, growing evidence indicates that sequence specificities can be more accurately captured by more complex techniques [2][3][4][5] . Recently, 'deep learning' has achieved record-breaking performance in a variety of information technology applications 6,7 . We adapted deep learning methods to the task of predicting sequence specificities and found that they compete favorably with the state of the art.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…Neural networks have become increasingly popular in recent years because of their tremendous success in image classification [1,2], speech recognition [3,4] and natural language processing tasks [5,6]. In fact, deep learning methods have regularly won many recent challenges in these domains [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Long short-term memory (LSTM) (Hochreiter and Schmidhuber, 1997) models solve this problem by introducing different gate functions that control the flow of information. This approach has been quite successful in tasks involving language models (Sutskever et al, 2014) and speech recognition (Graves et al, 2013). Meanwhile, breakthroughs in image captioning (Vinyals et al, 2015) have succeeded in transforming images into the language domain by combining the convolutional neural network (CNN) and recurrent models.…”
Section: Trends In the Development Of Ai Technology Applications Formentioning
confidence: 99%